Reduced right ventricular output reserve in patients with systemic sclerosis and mildly elevated pulmonary artery pressure - Nagel, Christian; Marra, Alberto M.; Benjamin, Nicola; Blank, Norbert; Cittadini, Antonio; Coghlan, Gerry; Distler, Oliver; Denton, Christopher P.; Egenlauf, Benjamin; Fiehn, Christoph; Fischer, Christine; Harutyunova, Satenik; et al. (Arthritis & rheumatology, 2019)
Objective This prospective study was undertaken to evaluate right ventricular function and pulmonary arterial compliance (PAC; ratio of stroke volume to pulse pressure) at rest and during exercise in patients with systemic sclerosis (SSc) with normal mean pulmonary artery pressure (PAP), patients with SSc with mildly elevated mean PAP, and patients with SSc with manifest pulmonary hypertension (PH). Methods Patients with SSc (n = 112) underwent clinical assessment and right-sided heart catheterization at rest and during exercise and were divided into 3 groups according to their resting mean PAP values: normal mean PAP (≤20 mm Hg), mildly elevated mean PAP (21-24 mm Hg), and PH (mean PAP ≥25 mm Hg). Results were compared between groups by analysis of variance followed by post hoc Student's t-test. Results Compared to patients with normal mean PAP, patients with mildly elevated mean PAP had a lower 6-minute walking distance (P = 0.008), lower cardiac index (P = 0.027) and higher pulmonary vascular resistance (P = 0.0002) during exercise, and lower PAC at rest (P = 0.016) and different stages of exercise (P = 0.033 for 25W and P = 0.024 for 75W). Conclusion The results of this study suggest that impaired 6-minute walking distance in SSc patients with mildly elevated mean PAP might be caused by reduced PAC during exercise and reduced right ventricular output reserve, presumably due to impaired coupling between the right ventricle and the pulmonary vasculature. These findings provide further evidence of the clinical relevance of mildly elevated mean PAP in patients with SSc.